Construction of Heroes in Guardians of The Galaxy (2014) - William Kristanto (Passage, 2018)
Guardians of the Galaxy (2014) directed by James Gunn presents a set of heroes that are different from the majorities of the other heroes, especially in terms of how they develop into heroes. The study examines the hero construction in Guardians of the Galaxy by using Campbell’s (2004) theory of hero construction as the theoretical guidelines. The qualitative method is used in this study to gain a deeper understanding of the construction. The findings show that the heroes are constructed in ways similar to the stages in Campbell’s theoretical proposition. The constructions are also very much influenced by external factors that the heroes meet. From the construction, the heroes in Guardians of the Galaxy are shown to develop from characters devoid of moral values, instead of characters with noble morals as frequently shown by the majorities of the other heroes. The heroes in Guardians of the Galaxy are also portrayed to have more human qualities in their construction which makes them more rounded. Keywords: hero, hero journey, hero construction, hero construction stages